2022
DOI: 10.3389/fbioe.2022.839756
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab-DTPA-Based PD-1 Imaging Reveals Structural and Pathological Changes in Colorectal Carcinoma

Abstract: Programmed cell death protein 1 (PD-1) expression is considered a prognostic marker of tumor response to the immuno-blocking therapy. In this study, nivolumab was conjugated with diethylenetriamine pentaacetate (DTPA) via condensation reaction between amidogen and p-SCN-Bn-DTPA, which provided labeling sites for 99mTc4+ or Gd3+ ions. SPECT and magnetic resonance T1 weighted imaging (T1WI) analyses were performed on mouse models of colorectal carcinoma expressing humanized PD-1 antigen. Furthermore, PD-1 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…As an alternative, molecular imaging of PD-1/PD-L1 expression can assist in analyzing tumor lesions and metastasis in real-time, providing repeatable, non-invasive and systematic monitoring of PD-1/PD-L1 expression. Currently, molecular radiological evaluation of PD-1/PD-L1 expression could be achieved using radiolabeled tracers consisting of antibodies, antibody fragments, targeted peptides, and small molecule inhibitors [92][93][94][95][96][97]. Interestingly, a high-impact clinical study using PD-L1-targeted 89 Zr-atezolizumab imaging confirmed that clinical responses in patients with lung, breast and bladder cancer were better correlated with pretreatment PET signal than with IHC or RNA-sequencing based predictive biomarkers [95].…”
Section: Imaging Of Programmed Cell Death Protein 1 and Its Ligandmentioning
confidence: 99%
“…As an alternative, molecular imaging of PD-1/PD-L1 expression can assist in analyzing tumor lesions and metastasis in real-time, providing repeatable, non-invasive and systematic monitoring of PD-1/PD-L1 expression. Currently, molecular radiological evaluation of PD-1/PD-L1 expression could be achieved using radiolabeled tracers consisting of antibodies, antibody fragments, targeted peptides, and small molecule inhibitors [92][93][94][95][96][97]. Interestingly, a high-impact clinical study using PD-L1-targeted 89 Zr-atezolizumab imaging confirmed that clinical responses in patients with lung, breast and bladder cancer were better correlated with pretreatment PET signal than with IHC or RNA-sequencing based predictive biomarkers [95].…”
Section: Imaging Of Programmed Cell Death Protein 1 and Its Ligandmentioning
confidence: 99%